RECONSTRUCTING IDENTITY THROUGH HISTORY EDUCATION: A STUDY ON CURRICULUM IMPLEMENTATION IN THE PHILIPPINES - Maria Grace E. Lucas (CV. Fahr Publishing, 2025)
This study explores how history education, as implemented through the Araling Panlipunan curriculum, contributes to the reconstruction of Filipino identity in Philippine secondary schools. The research specifically investigates how teachers interpret and deliver identity-related content, and how students engage with historical narratives in classroom contexts. Employing a qualitative case study approach, data were gathered through classroom observations, semi-structured interviews with teachers and students, and document analysis at San Lorenzo National High School in Central Luzon. The findings reveal a significant gap between the curriculum’s decolonial intentions and its practical implementation. Teachers expressed theoretical support for inclusive and critical history education but cited institutional constraints such as rigid syllabi, lack of training, and pressure to conform to standardized assessments. Students, meanwhile, demonstrated limited engagement with localized or critical historical perspectives, often viewing history as a subject focused on memorization. The study offers a novel contribution by integrating multi-actor perspectives—teachers, students, and curriculum—within a localized school setting, thus moving beyond content analysis to explore lived classroom experiences. It also highlights the underrepresentation of regional and indigenous narratives, stressing the importance of culturally responsive pedagogy. In conclusion, while policy-level reforms aim to promote national identity through history education, meaningful transformation remains hindered by structural and pedagogical barriers. To bridge this gap, a more holistic strategy is needed—one that empowers teachers, contextualizes content, and promotes active historical inquiry among students.